Letter from Newton K. Chase to Jane Tolmach - Newton K. Chase:::::: (1964)
Newton K. Chase informs Jane M. Tolmach that he has officially appointed her as a member of the State Central Committee. He states that the Committee will meet at the State Capitol on Sunday, August 16, at 10 a.m., the day after the State Convention. Chase explains that she may attend either in person or by proxy. If she cannot attend, she must complete and return the enclosed proxy form to the Secretary of State's office by 5 p.m. on Saturday, August 15.